2017
DOI: 10.5935/2525-5711.20170013
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent ameloblastoma 30 years after surgical treatment

Abstract: Introduction: Ameloblastoma is a locally invasive, slowly growing odontogenic epithelium, which can reach large proportions. It is preferentially located in the region of mandibular molars. The most indicated treatment is resection with safety margin, since its potential for recurrence is high. Objective: To report a case of recurrence the ameloblastoma. Case report: A 60-year-old female patient came to the hospital with difficulty speaking and eating because of the mass inside the mouth and earaches. The extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…A very long time has been reported between initial presentation and recurrence exactly like our patient who had 17 years between the initial presentation and the recurrence. Essaadi et al [7], de Miranda et al [10] and Vasan [11] reported a patient with recurrence in the bony graft 33, 30 and 28 years, respectively, after the initial presentation.…”
Section: Discussionmentioning
confidence: 99%
“…A very long time has been reported between initial presentation and recurrence exactly like our patient who had 17 years between the initial presentation and the recurrence. Essaadi et al [7], de Miranda et al [10] and Vasan [11] reported a patient with recurrence in the bony graft 33, 30 and 28 years, respectively, after the initial presentation.…”
Section: Discussionmentioning
confidence: 99%